MARKETING HEALTHCARE BEYOND BORDERS: A GLOBAL PERSPECTIVE ON MEDICAL TOURISM - Divinagracia, Sheryl S.; Yuesti, Anik (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
The globalization of healthcare has led to the emergence of medical tourism as a rapidly expanding industry, with countless marketing themselves as medical destinations. This study explores the intersection of healthcare and global marketing, analyzing how nations promote their medical services to attract international patients. It examines key marketing strategies, target markets, branding efforts and the implications of global healthcare promotion. The paper highlights the opportunities, ethical considerations and competitive challenges involved in marketing healthcare across borders.